2015
DOI: 10.5152/akd.2015.6185
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of metformin against doxorubicin cardiotoxicity in rats

Abstract: Objective:The clinical use of doxorubicin, which is a strong antineoplastic agent, is limited due to its cardiotoxic side effects. Metformin is a drug with antihyperglycemic effects, and it has been shown to have a cardioprotective effect on left ventricular function in experimental animal models of myocardial ischemia. The present study investigated the cardioprotective effect of metformin in rats with doxorubicin cardiotoxicity.Methods:Wistar albino rats were used in the study. Forty male, 10-week-old Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 38 publications
5
41
0
2
Order By: Relevance
“…In light of the prominent role of chemotherapy, anthracycline especially doxorubicin remains to be considered the footstone chemotherapy regimen of cancer treatment for a wide range of malignancies, particularly for breast cancer and lymphoma (2,3). Over decades from its discovery, the anti-tumor and cardiotoxic mechanisms of doxorubicin seem to continuously evoke considerable interest in basic science and clinical trial research.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the prominent role of chemotherapy, anthracycline especially doxorubicin remains to be considered the footstone chemotherapy regimen of cancer treatment for a wide range of malignancies, particularly for breast cancer and lymphoma (2,3). Over decades from its discovery, the anti-tumor and cardiotoxic mechanisms of doxorubicin seem to continuously evoke considerable interest in basic science and clinical trial research.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans are lacking 7 . Metformin, an oral antidiabetic agent, has proven in vitro benefit 8,9 . Studies in humans are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Many in vivo studies revealing the effects of metformin in alleviating the adverse side effects of doxorubicin have focused on biochemical changes such as reduction in free radical generation and mitochondrial damage (1, 8). The paper by Argun et al (9) entitled “Cardioprotective effect of metformin against doxorubicin cardiotoxicity in rats” published in this issue of the Anatolian Journal of Cardiology took a slightly different approach. In this in vivo study, the authors used echocardiography as a direct readout to demonstrate the beneficial effect of metformin.…”
mentioning
confidence: 99%
“…For example, recently, Chang et al (10) demonstrated the beneficial effects of angiotensin receptor blockers (ARBs) in preventing doxorubicin-induced cardiotoxicity in rats. Although the clinical application of ARBs for reducing doxorubicin-induced adverse effects is debatable, the use of metformin is so far reached now such that the study by Argun et al (9) should have much more translational value. To date, the majority of the clinical investigations have focused on cancer survival rate in type 2 diabetes patients.…”
mentioning
confidence: 99%